2019
DOI: 10.1016/j.actbio.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Mineral formation in the primary polyps of pocilloporoid corals

Abstract: In reef-building corals, larval settlement and its rapid calcification provides a unique opportunity to study the bio-calcium carbonate formation mechanism involving skeleton morphological changes. Here we investigate the mineral formation of primary polyps, just after settlement, in two taxa of the pocilloporoid corals: Stylophora pistillata (Esper, 1797) and Pocillopora acuta (Lamarck, 1816). We show that the initial mineral phase is nascent Mg-Calcite, with rod-like morphology in P. acuta, and dumbbell morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 86 publications
0
44
1
Order By: Relevance
“…Vesicles were previously identified in corals [72, 73]; however, their origin and content was not detailed and they are sometimes attributed to preservation byproducts. These intracellular ion-rich vesicles may endocytose sea water [74], after which they are enriched in carbonate ions and then form hydrated ACC and anhydrous ACC precursors stabilized by acidic biomolecules including CARPs [75]. Using cell cultures, Mass et al [61] suggest that the vesicles, which contain Asp rich proteins, then transport their contents to the ECM, releasing their content by exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Vesicles were previously identified in corals [72, 73]; however, their origin and content was not detailed and they are sometimes attributed to preservation byproducts. These intracellular ion-rich vesicles may endocytose sea water [74], after which they are enriched in carbonate ions and then form hydrated ACC and anhydrous ACC precursors stabilized by acidic biomolecules including CARPs [75]. Using cell cultures, Mass et al [61] suggest that the vesicles, which contain Asp rich proteins, then transport their contents to the ECM, releasing their content by exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite using low excitation power, Acropora muricata was particularly susceptible to CLSM. Quantitative comparisons to previous studies using conventional microscopy (WFM, CLSM and spinning disk confocal) for live imaging of Montipora capitata (Caldwell et al, 2017;Nielsen et al, 2018), Acropora digitifera (Ohno et al, 2017), Pocillopora damicornis and Stylophora pistillata (Mullen et al, 2016;Neder et al, 2019;Shapiro et al, 2016;Venn et al, 2009;Venn et al, 2011;Venn et al, 2013) was not possible as no power measurements were reported. Substantial differences in phototolerance may exist between different species.…”
Section: Discussionmentioning
confidence: 99%
“…They can also recover rapidly from environmental disturbances, making them important re-colonisers (Sweatman et al, 2011). Rather than using cell or tissue culture-based samples (Mass et al, 2012), single primary polyps (Neder et al, 2019;Ohno et al, 2017) or single polyps obtained through bail-out techniques (Shapiro et al, 2016), we here use small coral colonies with multiple polyps and a shared gastrovascular cavity. They allow the study of systemic responses in an unstressed, fully established colony.…”
Section: Fig 1 A) Size Of Commonly Used Samples and Of A Small Colonmentioning
confidence: 99%
See 2 more Smart Citations